ANALISIS TINGKAT LITERASI POLITIK TERHADAP INFORMASI KAMPANYE POLITIK PASCA PEMILU 2024 - Putra, Defna Nobirianto; Cahyono, Cahyono; Kania, Delila (Cahaya Ilmu Bangsa, 2025)
The year 2024 is a political year for the Indonesian people, because the second very important simultaneous general election (election) has taken place. The main focus will be on the simultaneous election to elect the President, Vice President, and members of the DPR, DPD, and DPRD, which was held on February 14, 2024. The important role of the 2024 election cannot be separated from the key role of political literacy itself, because political literacy provides space for democracy, so that people's understanding of political literacy can be achieved. Through political campaign information, voters, especially among young people such as students, make it easier to get to know their prospective leaders through various media. The purpose of this study is to determine the knowledge of political literacy, obstacles and efforts of students in finding information on the 2024 election political campaign. This research approach uses a qualitative research approach with a descriptive research method. Data collection is obtained through observation, interviews, and documentation. In this study, the subjects of the study were PPKn FKIP Pasundan University students. The results of the study show: 1) PPKn students know and understand the information on the 2024 election political campaign. This is proven by evidence of student participation in exercising their voting rights in the 2024 election and also participating in a series of election participant campaigns. 2) The obstacles faced by PPKn students in finding information on the political campaign are the emergence of negative campaign information such as false information (hoaxes), hate speech, which can worsen the political atmosphere in Indonesia. 3) PPKn students' efforts to overcome obstacles in obtaining information on the 2024 election political campaign are by conducting massive socialization regarding the election campaign to voters. In addition, there also needs to be socialization to students through discussions or seminars conducted by lecturers or academics, so that students' political literacy regarding political campaign information can be understood properly. Tahun 2024 adalah tahun politik oleh masyarakat Indonesia, karena dimana telah berlangsung pemilihan umum (pemilu) secara serentak kedua yang sangat penting. Fokus utama akan tertuju pada pemilu serentak untuk memilih Presiden, Wakil Presiden, serta anggota DPR, DPD, dan DPRD, yang telah dilaksanakan pada tanggal 14 Februari 2024. Peran penting pemilu 2024 tidak bisa lepas dari peran kunci dari literasi politik itu sendiri, karena literasi politik memberikan ruang gerak demokrasi, agar pemahaman masyarakat akan literasi politik dapat tercapai. Melalui informasi kampanye politik, para pemilih khususnya di kalangan muda seperti mahasiswa, memberikan kemudahan dalam mengenal calon pemimpinnya melalui berbagai media. Tujuan dari penelitian ini yaitu untuk mengetahui pengetahuan literasi politik, kendala dan upaya mahasiswa dalam mencari informasi kampanye politik pemilu 2024. Pendekatan penelitian ini menggunakan pendekatan penelitian kualitatif dengan metode penelitian deskriptif. Pengumpulan data diperoleh melalui observasi, wawancara, dan dokumentasi. Dalam penelitian ini yang menjadi subjek penelitian adalah mahasiswa PPKn FKIP Universitas Pasundan. Hasil penelitian menunjukan: 1) Mahasiswa PPKn mengetahui dan memahami informasi kampanye politik pemilu 2024. Hal ini dibuktikan dengan adanya bukti partisipasi mahasiswa dalam menggunakan hak pilihnya pada pemilu 2024 dan juga mengikuti rangkaian kampanye peserta pemilu. 2) Kendala Mahasiswa PPKn dalam mencari informasi kampanye politik tersebut, ialah adanya informasi kampanye negatif yang muncul seperti informasi palsu (hoaks), ujaran kebencian, yang dapat memperkeruh suasana politik di Indonesia. 3) Upaya mahasiswa PPKn dalam mengatasi kendala dalam memperoleh informasi kampanye politik pemilu 2024, dengan melakukan sosialisasi mengenai kampanye pemilu kepada pemilih secara masif. Selain itu, perlu adanya juga sosialisasi kepada mahasiswa melalui diskusi atau seminar yang dilakukan oleh dosen atau civitas akademika, agar literasi politik mahasiswa mengenai informasi kampanye politik dapat dipahami secara baik.